The Influence Of Organizational Factors on Compliance With The Standard Planning Process in Primary Health Care - Ayun Sriatmi; Sutopo Patria Jati; Eka Yunila Fatmasari (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2020)
Background: Planning becomes the most important management function because it arranges all management activities. Non-compliance with the standards of the planning process has an impact on the quality of planning that is unable to bridge needs which ultimately lead to dissatisfaction. PHC as public organizations must meet public service standards. Organizational factors are determinants of organizational performance as they relate to the provision and arrangement of vaious resourcesAims: The purpose of study was to determine affect of organizational factors on compliance with the standards of PHC planning process.Methods: An observational study with cross sectional design. All 56 PHC in the 2 districts in Central Java province (Semarang and Kudus) became the samples. The respondents are officer in charge of the PHC planning programme.. Data collection by interviews using questionnaires and observations. Data were analyzed descriptively and statistically.Results: Only 55.4% of PHCs comply with standard planning process. Weaknesses and inconsistencies still occur at every stage, especially with regard to inaccuracy of time, incomplete and inappropriate data, and low understanding of members of the team. Study shows that the aspect of manpower, infrastructure, organizing and monitoring-evaluation function are positively correlated with adherence to standard planning processes, where monitoring-evaluation factors are the dominant factor.Conclusion: All the gaps identified as the cause of puskesmas non-compliance to the standard planning process can be overcome through increasing staff commitment and competency by providing structured managerial training and routine socialization. Strengthening the monitoring-evaluation function needs to be pursued consistently to ensure the quality of the puskesmas planning process and the implementation of the work plan produced